Modelling bilateral intra-industry trade indexes with panel data: a semiparametric approach - Proença, Isabel (2022)
This paper focuses on the modelling of bilateral intra-industry trade indexes with panel data, applying a semiparametric approach. This extends the work of Papke and Wooldridge (J Econom 145: 121–133, 2008) for fractional responses, by introducing a nonparametric component to control for unobserved heterogeneity associated with the regressors. The proposed approach is based on the semi-mixed effects gen eralised linear model of Lombardía and Sperlich (Comput Stat Data Anal 56:2903– 2917, 2012), introduced in the context of small area statistics, and the semiparametric gravity model of Proença et al. (Empir Econ doi:10.1007/s00181-014-0891-x, 2014). The resulting nonlinear semiparametric model serves to explain the bilateral intra industry trade indexes between Portugal and the European Union, the BRIC emerging economies, and the five Portuguese-speaking African countries.